A regenerable porous carbon adsorbent for toluene adsorption and preparation method thereof
By mixing the carbon black with the binder and calcining treatment, a porous carbon adsorbent with excellent toluene adsorption performance was prepared, which solved the problem of low toluene adsorption efficiency in the prior art, and realized resource utilization and environmental protection.
Patent Information
- Application Number
- CN202111565376.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-12-20
AI Technical Summary
The prior art has low adsorption efficiency when dealing with volatile organic compounds (VOCs), especially toluene, and it is difficult to effectively utilize carbon-rich raw material carbon black, resulting in waste of resources and environmental pollution.
By mixing the carbon black with the binder and calcining under the action of the pore-forming agent, a renewable porous carbon adsorbent with excellent toluene adsorption properties was prepared.
It has achieved efficient adsorption of toluene, improved adsorption efficiency, and resourced utilization of discarded carbon black, reducing environmental pollution.
Smart Images

Figure CN114225906B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorbents, and in particular relates to a regenerable porous carbon adsorbent for toluene adsorption and a preparation method thereof. Background Art
[0002] Volatile organic compounds (VOCs) are common air pollutants emitted in the petrochemical and chemical industries. Common VOCs include benzene, aromatic hydrocarbons, aldehydes, ketones and alkane compounds. These VOCs not only harm the environment, such as water pollution, ozone layer depletion, and haze formation, but also pose a threat to the health of humans and animals, causing acute or chronic poisoning of the nervous system, blood system and immune system. Among them, benzene also has a high risk of carcinogenesis. At present, the main treatment technologies for VOCs include adsorption, absorption, condensation, catalytic oxidation and photocatalysis. Among them, adsorption is widely used because of its advantages of low treatment cost, simple process and good adsorption stability.
[0003] In VOCs adsorption treatment, commonly used adsorbents include molecular sieves, porous carbon, metal skeleton materials and mesoporous materials. Compared with other types of adsorbents, porous carbon has the advantages of wide range of raw materials, simple preparation, low price and easy desorption and regeneration, making it the most commonly used adsorbent.
[0004] Carbon black is a powdered carbon material produced by incomplete combustion or decomposition of hydrocarbons, mainly composed of carbon elements. In the process of partial oxidation of natural gas to produce acetylene, a large amount of by-product carbon black is generated. If these carbon blacks are burned directly, they will cause incomplete combustion due to their high water content (water content is more than 95%); if they are used in the rubber, coating and ink industries, their powdery structure will affect the product quality, and during the stacking process, they will also cause serious environmental pollution. However, carbon black has an ultra-high carbon content (carbon content is 90% to 99%) and a low mineral content. Its "rich carbon" is a necessary condition for the preparation of activated carbon with a high proportion of microporous structure, and the low mineral content can avoid chemical adsorption caused by minerals (such as alkali metals and alkaline earth metals). Therefore, we hope to use the advantages of carbon black with rich carbon and low mineral content as a raw material for preparing porous carbon, so as to obtain high-performance porous carbon materials, and also realize the resource utilization and environmental protection of carbon black resources. Summary of the invention
[0005] The object of the present invention is to provide a regenerable porous carbon adsorbent for toluene adsorption and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A renewable porous carbon adsorbent for toluene adsorption, the raw materials of which are carbon black and a binder, are prepared by calcining under the action of a pore-forming agent.
[0008] Preferably, the mass ratio of the carbon black to the binder is 95:5, and the binder is flour paste.
[0009] Preferably, the pore-forming agent is an aqueous solution of (NH4)2CO3, and the added amount of the (NH4)2CO3 is 20% of the total mass of the carbon black and the binder.
[0010] At the same time, the present invention also discloses a method for preparing a regenerable porous carbon adsorbent for toluene adsorption, comprising the following steps:
[0011] S1: Precursor preparation: After fully mixing carbon black and binder, add pore-forming agent, mix and stir thoroughly to obtain precursor;
[0012] S2: Drying: placing the precursor in an oven and drying at 90° C. for 24 h to obtain a dry material;
[0013] S3: Calcination: The dry material is placed in a muffle furnace and calcined to obtain a sample.
[0014] Preferably, the dry material is heated to 300° C. at a heating rate of 10° C. / min in a muffle furnace at room temperature, and then heated to 400-1000° C. at a heating rate of 5° C. / min and maintained for 2 h.
[0015] Technical effects and advantages of the present invention: The present invention successfully prepares a porous carbon adsorbent with excellent toluene adsorption performance by bonding carbon-rich raw material carbon black with a binder and using (NH4)2CO3 as a pore-forming agent under high-temperature pore-forming action. The PCBA prepared by the present invention has a developed micro / mesoporous structure, which can provide more adsorption sites for toluene molecules and has a higher adsorption efficiency, thereby realizing the resource utilization of waste carbon black and providing application possibilities for its VOCs adsorption, thereby realizing the resource utilization of carbon black resources and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is the SEM image of the porous carbon adsorbent;
[0017] Figure 2 It is the N2 adsorption-desorption isotherm of porous carbon adsorbent;
[0018] Figure 3 is the micropore size distribution (HK) diagram of the porous carbon adsorbent;
[0019] Figure 4 is the mesopore size distribution (BJH) diagram of the porous carbon adsorbent;
[0020] Figure 5Figure 2 shows the toluene adsorption and desorption of PCBA400.
[0021] Figure 6 Figure 2 shows the toluene adsorption and desorption of PCBA850;
[0022] Figure 7 Figure 2 shows the toluene adsorption and desorption of PCBA900. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] Example
[0025] A renewable porous carbon adsorbent for toluene adsorption, the raw materials of which are carbon black and a binder, are prepared by calcining under the action of a pore-forming agent.
[0026] The mass ratio of the carbon black to the binder is 95:5, and the binder is flour paste.
[0027] The pore-forming agent is an aqueous solution of (NH4)2CO3, and the added amount of the (NH4)2CO3 is 20% of the total mass of the carbon black and the binder.
[0028] At the same time, the present invention also discloses a method for preparing a regenerable porous carbon adsorbent for toluene adsorption, comprising the following steps:
[0029] S1: Preparation of precursor: Grind the block carbon black and dry it in an oven at 70°C for 48h, weigh 0.05g flour and put it into a crucible filled with 0.1ml deionized water, and add 0.95g carbon black powder, stir thoroughly, add (NH4)2CO3 aqueous solution, (NH4)2CO3 mass 0.2g, mix thoroughly and stir to obtain the precursor;
[0030] S2: Drying: placing the precursor in an oven and drying at 90° C. for 24 h to obtain a dry material;
[0031] S3: Calcination: The dry material is placed in a muffle furnace and calcined to obtain a sample. The dry material is heated to 300°C at a heating rate of 10°C / min in a muffle furnace at room temperature, and then heated to X°C at 5°C / min and maintained for 2h. The porous carbon adsorbents prepared when X is 400, 650, 700, 750, 800, 850, 900, 950 and 1000 are named PCBA400, PCBA650, PCBA700, PCBA750, PCBA800, PCBA850, PCBA900, PCBA950 and PCBA1000, respectively.
[0032] Evaluation of Toluene Adsorption and Desorption Performance of Porous Carbon Adsorbent
[0033] The toluene adsorption and desorption performance test of the porous carbon adsorbent was carried out in a micro-fixed reactor at normal pressure.
[0034] At 0°C, air is blown into liquid toluene to produce toluene vapor. The mixed gas flow rate is 20 ml / min and the toluene gas concentration is 33800 mg / m 3 . A U-shaped quartz tube containing 100 mg of porous carbon adsorbent was placed in a 20°C water bath, and the toluene concentration at the inlet and outlet was monitored by an online GC7890Ⅱ gas chromatograph equipped with a flame ionization detector. The toluene breakthrough time is the time required for the toluene concentration at the outlet to reach 5% of the toluene concentration at the inlet. The equilibrium adsorption time is the time required for the inlet and outlet to be equal. The equilibrium adsorption amount of toluene can be obtained by integrating the adsorption curve, and the integral formula is as follows:
[0035]
[0036] In formula (1.1),
[0037] q t (mg / g) is the toluene adsorption per unit mass of the adsorbent at time t;
[0038] m(g) is the mass of porous carbon adsorbent; v(m 3 / min) is the mixed gas flow rate;
[0039] ρ0(mg / m 3 ) are the toluene concentrations at the inlet and outlet at time t, respectively.
[0040] After the porous carbon adsorbent reached adsorption equilibrium, the toluene gas flow was turned off, and toluene was desorbed at an air flow rate of 20 ml / min at 20°C until the desorption equilibrium was reached.
[0041] Regenerative performance testing of porous carbon adsorbents
[0042] After the porous carbon adsorbent is subjected to three adsorption-desorption cycles at 20° C., if the toluene adsorption amount is lower than that of the previous cycle, the desorption temperature of the porous carbon adsorbent is increased before the next adsorption cycle.
[0043] The toluene adsorption and desorption performance evaluation experiment above obtained the toluene adsorption results of the porous carbon adsorbent at different pore-forming temperatures in the embodiment as shown in Table 1:
[0044] Table 1 Test data of toluene adsorption by porous carbon adsorbent prepared at different pore-forming temperatures
[0045]
[0046] From the evaluation results of the toluene adsorption performance of the above-mentioned porous carbon adsorbent, it can be seen that the porous carbon adsorbent produced under the conditions of the embodiments at different temperatures exhibits good toluene adsorption performance at a high pore-forming temperature (850°C); at the same time, the pore-forming temperature has a great influence on the toluene adsorption performance of the porous carbon adsorbent.
[0047] For example, the porous carbon adsorbent (PCBA400) prepared at a pore-forming temperature of 400°C has a saturated toluene adsorption capacity of only 97.1 mg / g;
[0048] When the pore-forming temperature is increased to 650℃ (PCBA650), the saturated toluene adsorption capacity can be increased to 130.8mg / g;
[0049] When the pore-forming temperature reaches 850℃, the toluene saturation adsorption capacity of the porous carbon adsorbent PCBA850 reaches the best, which is 298.9 mg / g;
[0050] Then, the pore-forming temperature was further increased to 1000°C, and the saturated adsorption amount of toluene by the porous carbon adsorbent PCBA1000 decreased to 228.5 mg / g.
[0051] According to the above results, it can be seen that the increase in pore-forming temperature has a certain effect on the toluene adsorption performance of porous carbon adsorbent, among which PCBA850 has the best toluene adsorption performance.
[0052] However, existing carbon-based adsorbents for toluene adsorption are generally made from biomass raw materials and need to be activated with phosphoric acid, and they do not show excellent toluene adsorption performance.
[0053] The PCBAs with different pore-forming temperatures in the embodiment were subjected to surface morphology analysis using a SEM scanning electron microscope.
[0054] The surface morphology of the PCBA with different pore-forming temperatures obtained by SEM analysis is as follows Figure 1 shown.
[0055] Depend on Figure 1It can be seen that the adsorbent PCBA400 presents a rough surface and a small amount of pore structure; when the pore-forming temperature rises to 650℃, the adsorbent surface gradually becomes uneven and the roughness further increases; as the pore-forming temperature further increases, its surface roughness continues to increase, showing obvious cracks and gaps, and obvious macropores can be seen in the adsorbent (PCBA900) with a pore-forming temperature of 900℃. It can be seen that the increase in pore-forming temperature can well promote the pore development of the adsorbent and the increase in surface roughness.
[0056] PCBA with different pore-forming temperatures in the embodiment was tested for N2 adsorption-desorption isotherms and pore size distribution of porous carbon adsorbent using a Bester 3H-2000 adsorption instrument at -196°C. Before the test, the sample was vacuum degassed at 300°C for 5h. The specific surface area of the sample was calculated by the BET equation, and the micropore size distribution and mesopore size distribution were calculated by the HK method and the BJH method, respectively.
[0057] The N2 adsorption-desorption isotherm curves and the corresponding pore size distribution curves of PCBA at different pore-forming temperatures are shown in the following figure: Figure 2 , Figure 3 , Figure 4 shown.
[0058] Depend on Figure 2 It can be seen that the prepared adsorbents show a combination of type I and type II isotherms of the H3 type hysteresis loop, indicating that the prepared adsorbents belong to porous materials. In the low-pressure stage (P / P0<0.01), the prepared adsorbents show a type I isotherm, which is attributed to the fact that a large amount of N2 is adsorbed by the micropores of the adsorbent, and the adsorption amount increases sharply; in the high-pressure stage (P / P0>0.8), the N2 adsorption of each adsorbent increases sharply, and an H3 type hysteresis loop is formed, which can be attributed to the capillary condensation of N2 molecules in the wide-pore mesoporous channel structure.
[0059] In addition, by Figure 3 , Figure 4 It can be seen that the size of the prepared adsorbent micropores is 0.6nm-0.8nm, and the mesopores show a wide pore size distribution. The above phenomenon shows that the prepared adsorbent is a porous material with a micro-mesoporous structure. Therefore, the PCBA prepared by the present invention has a developed micro / mesoporous structure, which can provide more adsorption sites for toluene molecules.
[0060] After PCBA with different pore-forming temperatures in the embodiment is subjected to three adsorption-desorption cycles at 20°C, if the toluene adsorption amount is lower than that of the previous time, the desorption temperature of the porous carbon adsorbent is increased before the next adsorption cycle, and the desorption temperatures are 60°C, 80°C, 100°C, and 120°C, respectively.
[0061] The reproducibility of porous carbon adsorbents PCBA400, PCBA850 and PCBA900 at different pore-forming temperatures is shown in the following table. Figure 5 , Figure 6 , Figure 7 shown.
[0062] During the first cycle of adsorption, the toluene adsorption of all samples decreased significantly, and the toluene adsorption of all samples in the first and second cycles was basically the same. With the increase of desorption temperature, the adsorption performance of all samples for toluene gradually recovered until their toluene adsorption performance reached the initial state. At the same time, PCBA850 showed obvious differences in toluene adsorption in the first cycle and final desorption temperature compared with the other two samples. Its toluene adsorption in the first cycle decreased the most, reaching 90.13 mg / g, and the final desorption temperature was also much higher than the other two samples, reaching 120°C. This phenomenon is attributed to the fact that PCBA850 has the best microporosity of 81.7%, and the rich pore structure causes toluene molecules to remain in the pores, requiring higher temperatures to be removed.
[0063] The present invention successfully prepares a porous carbon adsorbent with excellent toluene adsorption performance by bonding carbon-rich raw material carbon black with a binder and using (NH4)2CO3 as a pore-forming agent under high-temperature pore-forming action, thereby realizing the resource utilization of waste carbon black and providing application possibilities for its VOCs adsorption.
[0064] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
[0065] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A regenerable porous carbon adsorbent for toluene adsorption, characterized in that: Its raw materials are carbon black and binder, which are calcined under the action of pore-forming agent; The pore-forming agent is an aqueous solution of (NH4)2CO3, and the addition amount of the (NH4)2CO3 is 20% of the total mass of the carbon black and the binder; The mass ratio of the carbon black to the binder is 95:5, and the binder is flour paste.
2. A method for preparing a regenerable porous carbon adsorbent for toluene adsorption as claimed in claim 1, characterized in that: The steps include: S1: Precursor preparation: After fully mixing carbon black and binder, add pore-forming agent, mix and stir thoroughly to obtain precursor; S2: Drying: placing the precursor in an oven and drying at 90° C. for 24 h to obtain a dry material; S3: Calcination: The dry material is placed in a muffle furnace and calcined to obtain a sample.
3. The preparation method according to claim 2, characterized in that: The dried material was heated to 300°C at a heating rate of 10°C / min in a muffle furnace at room temperature, and then heated to 400-1000°C at a heating rate of 5°C / min and maintained for 2h.